Prevalence Of The Main Behavioral Risk Factors And Their Role In The Formation Of "Aggressive" Epidemiological Conditions In Relation To Cholelithiasis Among The Population Of Gerontological Age In The Fergana Valley (Results Of A Screening Study) - Mamasaliev N.S; Salakhidinov S.Z; Tursunov Kh.Kh; Kalandarov D.M (Zien Journals, 2025)
The article presents modern, foreign and domestic data on the problem of epidemiology, prevention and treatment of cholelithiasis (gallstone disease). The analysis of population studies and preventive programs forcholelithiasisin the population of the gerontological and geriatric group is carried out. The article discusses modern recommendations for the use of screening, various types of preventive studies, conservative and surgical methods of treatment of cholelithiasis.
Keywords: cholelithiasis; epidemiology; prevention